Lunar phobia in phyllostomid bats at La Ceiba, Tuxpan, Veracruz - Pech Canché, Juan Manuel; Coria Villegas, Paola Deniss; Chamorro-Florescano, Ivette Alicia; Alanís Méndez, José Lui; Lozano-Rodríguez, Miguel Ángel (Ecosistemas y Recursos Agropecuarios, 2018)
The term lunar phobia is used to explain the behavior that some nocturnal animals have to avoid periods with greater moonlight intensity. The aim was to determine the effect of the brightness of the new moon and the fullmoon on the richness, abundance and diversity of the phyllostomid bat community at the La Ceiba estate, Tuxpan, Veracruz, where the study was conducted from October 2013 to February 2014 using five mist nets for two nights per month. We captured 142 bats belonging to eight species, with Artibeus lituratus being the species with the highest records in both lunar phases (74 individuals). Although no signicant differences were found in diversity between the two lunar phases, greater cumulative species richness and abundance were recorded in the new moon (eight species, 118 individuals) than the full moon (five species, 24 individuals). The signicant decrease in abundance between the new moon and the full moon, mainly of small frugivorous species, indicates that lunar luminosity affects bat activity. It also has an effect on total species richness as three species were exclusively recorded in the new moon phase.